Os processos educativos em espaços não formais de educação na feira de economia solidária de Santa Maria/RS - Machado, Claudia Medianeira Rodrigues (2022)
The present work was developed in the Masters Course of the Graduate Program in Education at the Universidade Federal de Santa Maria, in the line of research “Educational Public Policies, Educational Practices and their Interfaces - LP2”. We start with the following problematizing question: “How do the educational processes occur among the fairgrounds of the Solidarity Economy Colonial Fair in Santa Maria/RS?”. As a general objective: “Understand how the educational processes occur among the fairgrounds of the Solidarity Economy Colonial Fair in Santa Maria/RS”. We established the following specific objectives: a) to map the profile of the interviewed stallholders who work at the Solidarity Economy Colonial Fair in Santa Maria/RS; b) identify and analyze the understanding of the interviewed stallholders about the Solidarity Economy; c) to analyze the educational processes that occur with the interviewed women who participate in the Solidarity Economy Colonial Fair/RS. The methodology consists of qualitative research. As data collection instruments, we used semi-structured interviews with five women marketers as the target audience. We analyzed the categories that emerged throughout the speeches resulting from the interviews, supported by the authors Brandão (1986), Boff (2001), Freire (2000), Filho (2004), Gadotti(1991) Gohn (2006), Gaiger (2013), Minayo (2002), Santos (2004), Singer (2012), among others. Through this work, we identified that educational processes strengthen ties related to the Solidarity Economy, good living, trust, exchanges and sharing of knowledge, self-management and fair prices. On the other hand, weaknesses in understanding the principles related to the Solidarity Economy, impacting participation and educational processes among the interviewed stallholders. Therefore, we understand the space of the Colonial Fair as a formative space for learning, socialization of knowledge exchanges and sharing through another possible and solidary world.